Técnicas de micropropagação e criopreservação para abacaxizeiro - Moraes, Ailton Melo de (2007)
Brazil is one of the three main pineapple producers in the world, being the state of Paraíba, especially, considered as the first of them. The area cultivated has slightly increased due to the small offer of good quality seedlings. This work aimed to develop a cv. EMEPA 1 micropropagation protocol especially selected to be cultivated in the state of Paraíba. The cv. EMEPA 1 axillary gems used were disinfested and inoculated in half MS solid with 5,8 pH. There was incubation in a growth room with temperature of 25 ± 5oC and photoperiod of 16 hours/light at a luminous intensity of 30 pmol.m-2.s-1, except for the etiolation phase, held at B.O.D, with no light and temperature of 28 ± 1oC. The cv. EMEPA 1 micropropagation protocol was developed according to the existing literature, comprising the following phases: treatment and isolation of explants (TI); establishing of explants (EE); etiolation (ES); regeneration (RE); multiplication (MU); extent; rooting ®; acclimatization (AC). A completely randomized design (CRD) was used in all the phases as follows: TI – CRD with 4 x 4 factorial array (4 concentrations of sodium hypochlorite x 4 exposition times to sodium hypochlorite), with 10 repetitions containing 1 explant per bottle; EE – DIC with 6 treatments comprised of 10 repetitions containing 1 explant per bottle; ES – CRD with 4 treatments, comprised of 10 repetitions containing 1 defoliated plantule per test tube; RE – DIC with 4 treatments, comprised of 10 repetitions containing 1 etiolated sprout per Petri’s plaque; MU – CRD with 8 treatments, comprised of 10 repetitions containing 1 explant per bottle; AL – CRD with 4 treatments comprised of 10 repetitions containing 1 plantule per bottle; and AC – CRD with 11 treatments, comprised of 4 repetitions containing 5 plants each. It was concluded that the concentration of 2% of sodium hypochlorite for 10 minutes causes gems disinfestation and the establishment can be carried out by means of tillage without any growth regulators. The etiolation can be achieved in MS with 1,86 mg.L-1 of ANA and regeneration in MS with 1,8mg.L-1 of ANA + 2,0 mg.L-1 of BAP. For the multiplication, the type of tillage indicated is MS supplemented with 2,0 mg.L-1 of BAP + 0,5 mg.L-1 of ANA.; in extent, the type of crop MS without any dilution causes the highest growth of plantules, whereas the addition of ANA prompts increase in number and decrease of plantules root size and the organic compound favors increase and development of pineapple plantules produced in vitro during the acclimatizing phase.